2015
DOI: 10.1371/journal.pone.0130502
|View full text |Cite
|
Sign up to set email alerts
|

The Early-Onset Myocardial Infarction Associated PHACTR1 Gene Regulates Skeletal and Cardiac Alpha-Actin Gene Expression

Abstract: The phosphatase and actin regulator 1 (PHACTR1) locus is a very commonly identified hit in genome-wide association studies investigating coronary artery disease and myocardial infarction (MI). However, the function of PHACTR1 in the heart is still unknown. We characterized the mechanisms regulating Phactr1 expression in the heart, used adenoviral gene delivery to investigate the effects of Phactr1 on cardiac function, and analyzed the relationship between MI associated PHACTR1 allele and cardiac function in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…We further ranked the KDs based on additional layers of data-rich analyses to provide high-confidence candidate genes for CAD. Our analyses not only detected well-implicated CAD disease genes such as lipid genes, COL4A2 , and CXCL12 3436 but also unraveled novel key regulators for CAD such as LUM , HGD , F2 , ANXA3 , and STAT3 .…”
Section: Discussionmentioning
confidence: 70%
“…We further ranked the KDs based on additional layers of data-rich analyses to provide high-confidence candidate genes for CAD. Our analyses not only detected well-implicated CAD disease genes such as lipid genes, COL4A2 , and CXCL12 3436 but also unraveled novel key regulators for CAD such as LUM , HGD , F2 , ANXA3 , and STAT3 .…”
Section: Discussionmentioning
confidence: 70%
“…37 In rats, PHACTR1 is also down-regulated following myocardial infarction and may play a role in regulating the relative expression of actin isoforms in the heart. 38 ddPCR™ was used to confirm the differential expression of these transcripts (Figure 3A–E). …”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies revealed a pivotal role in vascular tube formation and actin polymerization [40•, 41•] Upregulation of PHACTR1 by TGFβ has been described [42•], potentially pointing to a connection with the TGFβ signaling pathway. A role in mechanotransduction has also been suggested [67]. …”
Section: Role Of Genetic Risk Factors In Common Multifactorial Strokementioning
confidence: 99%